On the influence of TiB2, TiC, and TiN hard particles on the microstructure of localized laser dispersed AISI D2 tool steel surfaces - Spranger, Felix; Schirdewahn, Stephan; Kromm, Arne; Merklein, Marion; Hilgenberg, Kai (Journal of Laser Applications, 2020)
The control of friction and wear is a major concern in many industrial applications. A promising method for tailored surface modification is the so-called laser implantation technique. This method combines surface texturing and material optimization in one processing step by a localized dispersing of hard ceramic particles using pulsed laser radiation. Wear resistant, protruding micrometric features (implants) with defined geometry can be created in a deterministic pattern where needed on highly stressed surfaces, i.e., on forming or cutting tools. However, in order to maintain the implants over the tool's lifetime, a suitable selection of hard ceramic particles is a prerequisite. They must provide a defect-free metal matrix composite with a high share of homogeneously distributed particles and, especially, high implant hardness. In this study, TiN, TiC, and TiB2 hard particles were compared as implant materials for the first time. By a systematic variation of pulse power and pulse duration, their dispersing behavior and influence on the material properties of AISI D2 tool steel were investigated. Although all powder materials had grain sizes smaller than 10 mu m, it was possible to disperse them by pulsed laser radiation and to obtain defect-free protruding implants. The highest share of dispersed particles (similar to 64%) was observed for TiB2. By scanning electron microscopy and energy dispersive x-ray spectroscopy, it was also shown that a significant share of the preplaced particles was dissolved by the laser beam and precipitated as nanometer sized particles within the matrix during solidification. These in situ formed particles have a decisive influence on the material properties. While the TiN and TiC implants have shown maximum hardness values of 750 and 850 HV1, the TiB2 implants have shown the highest hardness values with more than 1600 HV1. By x-ray diffraction, it was possible to ascribe the lower hardness values of TiC and TiN implants to high amounts of retained austenite in the metal matrix. By implanting TiB2, the formation of retained austenite was successfully suppressed due to the in situ formation of TiC particles, which was proven by electron backscatter diffraction. In conclusion, all the implant materials are basically suitable for laser implantation on AISI D2 tool steel. However, TiB2 has shown the most promising results.
CRIS-Team WoS Importer:2020-05-22